Right to Access Social Housing in the Perspective of International Human Rights Law and Vietnam’s Regulations - Nguyen, Yen Thi Hong; Nguyen, Hoi Van (Journal of Southeast Asian Human Rights, 2024)
Housing is one of the basic needs of each individual, family and society. This right has also been widely recognized in international human rights instruments at the global, regional and national levels. The general comments of the United Nations convention committees also point out that the right to housing is not simply the right to have a place to reside but also refers to many different aspects of maintaining residence and the surrounding living conditions. The explanations also mentioned the responsibility of countries to ensure access to housing for particular groups in society and consider it as a part of social security policy. Although it is a developing country with many difficulties and challenges in economic development, from a very early age, Vietnam has paid special attention to fundamental human rights, particularly the right to housing. Although specific outcomes have been achieved, there are perspectives that the quantity and total area of social housing constructed still need to satisfy the objectives established in the National Housing Development Strategy 2020 and vision for 2030. In addition, implementing related regulations remains plagued with challenges and concerns. From the situation, the article will focus on  (i) clarifying the legal and practical issues of ensuring access to social housing at international and national levels and (ii) pointing out the challenges and legal gaps in this field in Vietnam. From there, (iii) providing suggestions for Vietnam to implement effectively this right of Vietnamese citizens in the coming time. Keywords: Right to Housing, the Human Right to Adequate Housing, Social Housing, Human Rights, Individual’s Rights